Anglia XVIII wieku widziana okiem Johna Adamsa - Grobis, Jerzy (Acta Universitatis Lodziensis. Folia Historica, 1985)
The article represents a fragment of a bigger entity devoted to European affairs as presented in J. Adams’ Journals. John Adams was one of the (leaders of the) American revolution. In the long process of getting to know Europe, J. Adams passed through several stages, and the first one of them was getting acquainted with England the country from which his ancestors came. This was done through contacts with the European (mainly English) books easily accessible in the American market. His deliberations on books of Hobbes, Lock, Harrington, emotions experienced when reading Milton's and Shakespeare’s masterpieces provided a foundation on which his vision ot Europe was built. He was indebted to the English translators for his familiarity with Rousseau, Montesquieu, Grotius, Puffendorf, and Machiavelli. This represented an Anglo-Saxon trend in intellectual pursuits of an American lawyer. Another channel allowing him to get „get acquainted" with Europe was his knowledge of Greek and Latin acquired at Harvard, which would allow (him to get an insight into treasures of the antique literature. Nonetheless, his interests were focussed on the English law and its political system of which he was a devoted adherent. While pondering over the concept of „common sense” in the English legislation and on the unique construction of the English constitution, John Adams reached a conclusion that it was the most stable and elastic legal system in the world. This led to an attempt at its application for objectives of the American revolution. J. Adams was a politician, who unlike the radicals would try to adapt the English system of law to conditions prevailing at the time of the revolution without, however, destroying it.